HUBUNGAN LOCUS OF CONTROL INTERNAL DENGAN KEMATANGAN KARIR PADA SISWA SMKN 1 PERCUT SEI TUAN - Siregar, Mulia (Psychology Department Faculty of Psychology Universitas Medan Area, 2015)
Career maturity is the success of someone in completing tasks typical of career development atthe stage of certained development. Internal locus of control is an individuals belief that theevents that happened (successes and failures) as a result of an effort or his behavior. Measuringinternal locus of control using a scale IE compiled by Rotter (1966) and adapted by researcher.Measuring career maturity used CMI arranged by Crites and adapted to the culture ofIndonesia by Taganing, et al (2006). This study involves 90 students of class XI and XII ofSMKN 1 Percut Sei Tuan Department of Mapping Survey and Construction of Concrete Stone.Sampling technique used total sampling because the researcher took the total population for theresearch sample. It can be concluded that there is a significant relationship between thevariables XY, obtained r xy = 0.674; p = 0.000 (p <0.010) which means that the hypothesisotherwise accepted. The effective contribution internal locus of control on career maturity of45.5%.